Language change : linguistic imperialism or empowerment? : observations on the use of English in contemporary urban Samoa : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Anthropology at Massey University, Albany, New Zealand - Vague, Phillipa (Massey University, 2014)
English is widely considered to be a global language, the lingua franca of the modern world, and the language of globalisation. For some cultures, this English imperialism equates to the loss of their indigenous language(s). Amidst growing concerns that language loss is occurring in the Pacific, this research seeks to explore the use and purpose of English in contemporary urban Samoa, and considers the effect this is having on Gagana Samoa – the Samoan language. Drawing on Pierre Bourdieu’s practice theory, this study argues that English occupies an important place in Samoan society as it possesses symbolic and economic capital which can be utilised by both individuals and family units, within Samoa and overseas. Furthermore I explore the role of music in English language acquisition and use, and assert that music is a means of gaining symbolic capital within Samoan society. Finally I discuss Samoan perspectives of language change and consider the future of the English and Samoan languages in Apia. The fieldwork for this research was conducted over a period of six weeks in the village of Moata’a, and the wider Apia area in Upolu, Samoa. My research methods consisted of participant observation, discussions with key informants and informal interviews. I also carried out observations at three early educational establishments, Sunday school, preschool and primary school.
Keywords: English language; Linguistic change; Samoa; Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics::Other Germanic languages::English language